The Effects of Complementary Alternative Methods in Labor on Fear of Birth, Birth Satisfaction, and Childbirth Perceptions - Okyay, Esra Karataş; Barut, Sümeyye (Selcuk University, 2025)
Aim: This research was conducted to compare the fear of birth, birth satisfaction, and childbirth perceptions of postpartum women using complementary alternative methods (CAMs) in labor. Methods: This descriptive, cross-sectional study was conducted with 391 volunteer pregnant women at a university hospital in Türkiye. Data were collected in two stages: during pregnancy and at the end of delivery. A personal information form was completed by face-to-face interview at 37-41 weeks of pregnancy. At the end of delivery, the puerperants were contacted by phone for questions about CAMs they used in their deliveries, Traumatic Childbirth Perception Scale (TCPS), Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) Version B and Birth Satisfaction Scale-Short (BSS-S) Form were applied. Results: 69.8% of women used CAMs during delivery. In the regression model, younger maternal age (OR:0.933), being a high school (OR:2.343) and university graduate (OR:2.165), moderate-income level (OR:7.259), being primiparous (OR:0.489), participation in prenatal education classes (OR:0.320), and receiving 4 or more prenatal care (OR:2.476) were determined to be the predictors of the use of CAMs at birth. İt was determined that the mean score of the W-DEQ Version B of those using CAMs was significantly lower than those not using CAMs (p=0.024) and the mean score of the BSS-R was significantly higher (p<0.001). Conclusion: In the study, it was determined that postpartum women using CAMs experienced less fear of birth and had higher birth satisfaction. © 2025, Selcuk University. All rights reserved.
Doğumdaki Tamamlayıcı Alternatif Yöntemlerin Doğum Korkusuna, Doğum Memnuniyetine ve Doğum Algısına Etkisi
Keywords: Birth satisfaction; complementary alternative methods; fear of birth; postpartum; traumatic childbirth perception